Teacher agency within the context of formative teacher assessment: an in-depth analysis. Issue 5 (19th October 2016) - Verberg, Christel P. M.; Tigelaar, Dineke E. H.; van Veen, Klaas; Verloop, Nico
Abstract: Teachers' agency has an effect on their own learning process at the workplace. In this study we explored the extent to which teachers participating in a formative teacher assessment procedure developed a sense of agency. We investigated not only whether teachers participating in a such an assessment procedure experienced agency and thus felt in control of the learning process and able to pursue their learning objectives, but also whether agency was visible, by looking at decision-making in real time: did teachers take an active role in their own assessment, especially regarding the learning objectives to be pursued, during the assessment meetings? We found that teachers experienced a high level of agency while participating in the assessment procedure, but did not consistently show this during the assessment procedure.